Representasi Feminisme dalam Novel Namaku Dahlia karya Syafrizaldi - Fathdiah Purwasari; Suntoko Suntoko; Een Nurhasanah (Faculty of Languages and Arts, Universitas Negeri Padang, 2021)
This research is based on the fact that novels are still popular in Indonesia with a background of women who are portrayed as weak creatures compared to men from all aspects. Novels with a theme like this are still very popular today, even though novels are one of the media to convey information to society so that people's perceptions of women are shaped like that. The purpose of this research is to describe the representation of feminism in the economic and social aspects of the novel Namaku Dahlia. The type of research used in this research is qualitative descriptive analytical method. The data source in this research is the novel Namaku Dahlia by Syafrizaldi. The data collection technique used is literature. The theory used in this research is feminism. The results of this study indicate that the novel Namaku Dahlia contains feminist ideas specifically in the economic and social fields. The results showed that there were four data representing feminism on the economic aspect and three data representing feminism on the social aspect.